Peran Orang Tua dalam Meningkatkan Motivasi Menghafal Al-Quran Santri di Rumah Tahfidz Thoriqul Quran Samarinda - Nadia Nurindah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
Parents are the primary educators and have a significant impact on building children’s love for the Qur’an from an early age. Their motivation becomes a psychological support that helps students overcome obstacles in maintaining and improving their memorization. This research aims to explore the parental role along with the supporting and inhibiting factors experienced by parents in motivating students at Qur’anic memorization house of Thoriqul Qur’an Samarinda. Using a qualitative approach, data were collected through observation, interviews, and documentation, then analyzed using role and motivation theory. The results show that parents contribute to enhancing children’s motivation through roles as educators, motivators, role models, counselors, supervisors, and facilitators. Encouragement, Qur’anic habits at home, advice, rewards, and supervision positively influence memorization, although role-modeling in memorization is not yet optimal. Supporting factors include aspirations for pious children, good religious understanding, and adequate economy, while barriers include economic hardship and an unsupportive environment.